Saberes geométricos para a formação de professores primários em Sergipe : uma investigação sobre o período de 1890 a 1944 - Resende, Maria José de (2018)
This work presents the result of a research that had as objective to examine how were prescribed the geometric knowledge for the formation of primary teachers in Sergipe in the period from 1890 to 1944. For this, the sources used were official documents like Decrees, Laws, Regulations, Teaching programs and pedagogical journals in order to identify and characterize geometric knowledge in the training of primary teachers. They were consulted as reference: Valente (2005, 2013) regarding the understanding about the production in history of mathematical education; Leme da Silva (2015) on the understanding of geometric knowledge; Chervel (1990) on the constituents and purposes of a discipline, among other authors. Initially, the research used the documentary study, examining sources from the period from 1890 to 1931, with the purpose of understanding and identifying the geometric knowledge in the formation of normalists in the period before the 1930s. made it possible to compare the geometric knowledge that was proposed for the Normal Course and the Primary Course. According to the Teaching Programs, the geometric knowledge in the Primary Course constituted the subject / discipline Drawing (Linear Design), being recommended in some moments by means of the free drawing, the drawing of geometric figures and, in Arithmetica, approaching "surface , perimeter, area evaluation, relation between diameter and circumference "; for the Normal Course, the geometric knowledge had a more specific treatment with a level of deepening, for example, in relation to the treatment of theories like: "theory of perpendiculars"; "Theory of parallels"; "Polygonos theory". With regard to the teaching method proposed, at the time in Sergipe, we can highlight two moments: the first in the period of 1890 - 1930, whose teaching method recommended in the official documents were intuitive; and the period 1930-1940, with indications of the change of method, going to the active method. The latter can be identified in the guidelines proposed to teachers, under two scopes: in the pedagogical magazines located in the collection of the Epifânio Dórea Library (which probably circulated in this State) and in the organization of geometric knowledge, from the Teaching Programs.